Role of the CCL2‐CCR2 signalling axis in cancer: Mechanisms and therapeutic targeting - Xu, Maosen; Wang, Yang; Xia, Ruolan; Wei, Yuquan; Wei, Xiawei (Cell proliferation, 2021)
The chemokine ligand CCL2 and its receptor CCR2 are implicated in the initiation and progression of various cancers. CCL2 can activate tumour cell growth and proliferation through a variety of mechanisms. By interacting with CCR2, CCL2 promotes cancer cell migration and recruits immunosuppressive cells to the tumour microenvironment, favouring cancer development. Over the last several decades, a series of studies have been conducted to explore the CCL2‐CCR2 signalling axis function in malignancies. Therapeutic strategies targeting the CCL2‐ CCR2 axis have also shown promising effects, enriching our approaches for fighting against cancer. In this review, we summarize the role of the CCL2‐CCR2 signalling axis in tumorigenesis and highlight recent studies on CCL2‐CCR2 targeted therapy, focusing on preclinical studies and clinical trials. The chemokine ligand CCL2 and its receptor CCR2 are implicated in the initiation and progression of various cancers. The CCL2‐CCR2 signalling axis plays a critical role in the promotion of pathological angiogenesis, the survival and invasion of tumour cells, and the recruitment of immune inhibitory cells. Therefore, CCL2 and CCR2 enable us to explore the sophisticated mechanisms underlying cancer development and provide potential options for treating malignant tumours.